Discovery of new nicotinamides as apoptotic VEGFR-2 inhibitors: virtual screening, synthesis, anti-proliferative, immunomodulatory, ADMET, toxicity, and molecular dynamic simulation studies - Reda G. Yousef; Albaraa Ibrahim; Mohamed M. Khalifa; Wagdy M. Eldehna; Ibraheem M. M. Gobaara; Ahmed B. M. Mehany; Eslam B. Elkaeed; Aisha A. Alsfouk; Ahmed M. Metwaly; Ibrahim H. Eissa (Taylor & Francis Group, 2022)
A library of modified VEGFR-2 inhibitors was designed as VEGFR-2 inhibitors. Virtual screening was conducted for the hypothetical library using in silico docking, ADMET, and toxicity studies. Four compounds exhibited high in silico affinity against VEGFR-2 and an acceptable range of the drug-likeness. These compounds were synthesised and subjected to in vitro cytotoxicity assay against two cancer cell lines besides VEGFR-2 inhibitory determination. Compound D-1 showed cytotoxic activity against HCT-116 cells almost double that of sorafenib. Compounds A-1, C-6, and D-1 showed good IC50 values against VEGFR-2. Compound D-1 markedly increased the levels of caspase-8 and BAX expression and decreased the anti-apoptotic Bcl-2 level. Additionally, compound D-1 caused cell cycle arrest at pre-G1 and G2-M phases in HCT-116 cells and induced apoptosis at both early and late apoptotic stages. Compound D-1 decreased the level of TNF-α and IL6 and inhibited TNF-α and IL6. MD simulations studies were performed over 100 ns.